Metrics for optimum allocation of resources on the composition and characterization of crop collections: The CIMMYT wheat collection as a proof of concept - Reyes-Valdés, M. Humberto; Burgueño, Juan; Sansaloni, Carolina Paola; Payne, Thomas S.; Pacheco Gil, R. Angela; González-Cortés, Areli (Southern Cross Publishing, 2022)
Crop genebank collections are important resources for preserving genetic diversity to face the worldwide demand for food and coping with crop diseases and climate change. However, genebanks tend to accumulate materials without systematic collection growth. Thus, tools for optimizing collections are expected to help improvement of genebanks quality. Furthermore, the genotyping efforts of genebanks would benefit from tools that can help to sample the accessions. A set of parameters to aid the optimization of genebanks are defined, in which Relative Balance is central. In this study, the foundation of our mathematical approach was Kullback-Leibler divergence, providing formulas with consistent properties. Two examples were used as proof of concept. The first one was the comparison between actual and putative optimal numbers of accessions in the Triticum set of the CIMMYT (Centro Internacional de Mejoramiento de Maíz y Trigo) Wheat Germplasm Bank, with 135,236 entries classified into ten groups. The second one was based on a set containing Triticum plus eight related genera, with 159,741 accessions classified into 217 end-groups, with the goal of illustrating the use of the analytical tools to optimize the ongoing genotyping process. The first example shows a scenario with a well-balanced allocation of accessions. The second example illustrates the optimized choice of end-groups to add 10,000 accessions to the genotyping process. The proof of concept showed the consistency and usefulness of the proposed methods for the improvement of composition in collections and their characterization